Validated Outcome Measures and Postsurgical Scar Assessment Instruments in Eyelid Surgery: A Systematic Review. Issue 7 (July 2021) - Ramanathan, Diya; Chu, Sherman; Prendes, Mark; Carroll, Bryan T.
Abstract : BACKGROUND: Determining which postsurgical scar assessment instruments, if any, cover important eyelid outcome measures can either attest to the strength of one or more instruments or reveal the need for a more comprehensive scale. OBJECTIVE: To systematically review validated outcome measures after eyelid surgery and postsurgical scar assessment tools to see whether any individual or combination of 2 assessment tools encompass all relevant, validated eyelid outcome measures. METHODS: Systematic reviews of validated eyelid outcome measures and postsurgical scar assessment tools were conducted using PubMed/MEDLINE and Ovid. Outcome measure papers that met inclusion criteria were sorted into 8 categories: Patient Subjective, Visual Function, Mechanical Function, Daily Activities, Adverse Effects, Aesthetic Quantitative: Clinical Measurements, Aesthetic Qualitative: Global, and Aesthetic Qualitative: Specific. Outcome measure papers were categorized into tiers of evidence support, and assessment tools were evaluated based on which outcome measures each covered. RESULTS: No one or combination of 2 assessment tools covered all selected eyelid outcome measures. Although measures related to the subjective patient experience were included in several of the assessment scales, none covered measures of visual function or eyelid-specific clinical measurements. CONCLUSION: There is currently no existing postsurgical scar assessment instrument that covers all important eyelid-specific outcome measures. Abstract : Supplemental Digital Content is Available in the Text.